Memperkuat Kemampuan Mendengar melalui Refleksi Pembelajaran: Panduan Praktis untuk Siswa dan Guru - Ilmiani, Aulia Mustika; Rahman, Nur Fuadi; Prasasti, Khoeriyah Ajeng (Postgraduate of IAIN Metro Lampung Indonesia, 2023)
This research discusses the steps of Arabic language learning reflection that can improve students' listening skills. The research method used is a qualitative method with a narrative approach. The research data was collected from in-depth interviews, participant observation, and document analysis. The data generated were in the form of interview transcripts, field notes, observation notes, written documents, and video recordings. As for analyzing the data, the researcher used a narrative approach that involved the process of reading and understanding the data that had been collected, then identifying the main patterns and themes that emerged from the data. Furthermore, researchers categorized, compared, and connected these themes to make interpretations and understand the meaning obtained. The findings of this study show that activities such as listening then guessing style, listening then expressing meaning, listening then making sentences, and listening then writing sentences quickly can help improve students' listening skills. This research shows that although the use of innovative methods and media in Arabic language learning is quite diverse, there are still various problems that have not been covered, especially in terms of students' listening skills. The novelty of this study lies in the focus on strengthening learning reflection which can be a guide for teachers to improve the quality of their learning.